2009
DOI: 10.1021/je900440t
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Vapor−Liquid Equilibrium Data of 1,1,1,2-Tetrafluoroethane (R134a) + Dimethylformamide (DMF) Working Fluids for an Absorption Heat Transformer

Abstract: Vapor-liquid equilibrium data of 1,1,1,2-tetrafluoroethane (R134a) + dimethylformamide (DMF) were measured in the temperature range from (303.30 to 353.24) K by the static analytic method. The results are of interest to test the possibility of using R134a as a refrigerant in combination with an organic absorbent, that is, DMF, in an absorption heat transformer. The experimental data are correlated using the Peng-Robinson equation of state in combination with the Mathias-Copeman R function, MHV1 mixing rules, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 13 publications
1
31
0
Order By: Relevance
“…Previous works carried out by the same present authors are reported in the literature and one can cite Zehioua et al 2,3 . who considered the modeling and experimental measurements of isothermal vapor-liquid equilibrium data for different binary systems namely 1, 1, 1, 2-Tetrafluoroethane (R134a) + Dimethylformamide (DMF) working fluids used for an Absorption Heat Transformer (AHT) 2 and R134a + 1-Methoxy-2-(2methoxyethoxy) ethane (DMEDEG) and 1,2-bis(2-ethoxyethoxy) ethane (DMETrEG) 3 . Also…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Previous works carried out by the same present authors are reported in the literature and one can cite Zehioua et al 2,3 . who considered the modeling and experimental measurements of isothermal vapor-liquid equilibrium data for different binary systems namely 1, 1, 1, 2-Tetrafluoroethane (R134a) + Dimethylformamide (DMF) working fluids used for an Absorption Heat Transformer (AHT) 2 and R134a + 1-Methoxy-2-(2methoxyethoxy) ethane (DMEDEG) and 1,2-bis(2-ethoxyethoxy) ethane (DMETrEG) 3 . Also…”
Section: Introductionsupporting
confidence: 64%
“…This latter has already been described in details by Laugier and Richon 7 . Also a detailed description of the used apparatus and the adopted experimental procedure were given by Zehioua et al 2 . The equilibrium temperature was measured using two (Pt-100) platinum probes where a priori a 25 Ω reference platinum probe (Tinsley, France) was used to calibrate both temperature sensors.…”
Section: Apparatus and Experimental Proceduresmentioning
confidence: 99%
“…The detail of the experimental setup has been discussed in our previous manuscript 7 . The equipment is the same used by Zehioua et al 8 and the procedure is identical to…”
Section: Methodsmentioning
confidence: 99%
“…The experimental work has been carried out at CEP-TEP (Centre Eńergetique et Procedeś), MINES ParisTech, France, where a "static−analytic" technique based apparatus consisting of an equilibrium cell equipped with one moveable rapid online sampler injector (ROLSI) was used. The equipment is identical to the one used by Zehioua et al, 6 and the procedure is identical to Coquelet et al 7 The ROLSI sampler is capable of making vapor−liquid samples without disturbing the equilibrium concentration and pressure, since the size of the samples (less than 1 μL) is negligible compared to the volume of the cell, that is, 20 cm 3 . The liquid and vapor samples are analyzed using a gas chromatograph (Varian model CP-3800), equipped with a thermal conductivity detector (TCD), and a flame ionization detector (FID).…”
Section: Methodsmentioning
confidence: 99%